Current Aspects of Medical Rehabilitation of Patients with Cancer Related Lymphedema of Extremities: a Narrative Review - Tatiana V. Konchugova; Tatiana V. Apkhanova; Detelina B. Kulchitskaya; Olga V. Yurova; Lev G. Agasarov; Tatyana V. Marfina (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Over the past decades, in developed countries and in the Russian Federation, there has been an increase in the number of patients with secondary lymphedema who have undergone surgical treatment with dissection of regional lymph nodes and radiation therapy for various forms of gynecological cancer in women and prostate cancer in men, as well as breast cancer. AIM. Search and analysis of the results of previously published randomized controlled trials (RCTs) of the effectiveness of various non-drug rehabilitation methods in patients with lymphedema of the extremities who underwent radical treatment for cancer of various locations. MATERIALS AND METHODS. A search was conducted and studied publications in international scientific peer-reviewed publications (PEDro Database) on medical rehabilitation for cancer treatment-related lymphedema (LSPR) for the period from 1996 to December 2023 using the keywords "lymphedema", "rehabilitation". 145 RCTs focused on medical rehabilitation and conservative treatment of LSPR. DISCUSSION. Lifestyle correction and psychosocial interventions are recommended to improve the quality of life of patients. Studies have found that early activation, various physical exercises with a slow increase in loads under the supervision of a physical therapist are safe and help increase endurance, strength and range of motion in a limb with lymphatic edema. The clinical effectiveness of therapeutic exercises in the pool has been proven, manifested in the reduction of edema in patients with LSPR. The effectiveness of compression products with Velcro technology as an alternative to rigid low-stretch bandages in patients with LSPR has been confirmed. The anti-edematous and anti-inflammatory effects of low-intensity laser therapy and magnetic therapy in the rehabilitation of patients with LSLR have been proven. Alternating pneumatic compression (APC) is recommended as an adjuvant treatment in addition to comprehensive decongestant therapy. Preference should be given to the use of technologies of advanced hardware lymphatic drainage methods that imitate manual techniques. CONCLUSION. To improve the physical and socio-psychological functioning of patients with LSPR, an integrated approach is required, including lifestyle changes, psychological correction, compression therapy, modern exercise therapy techniques, and safe physiotherapeutic technologies. Conducted scientific research indicates the high effectiveness of the use of manual and hardware lymphatic drainage techniques, while the use of PPC is more economical and accessible, and does not require the involvement of specialists who know the expensive method of manual lymphatic drainage.